Amelija Mažylytės (1900–1972) merit in the development of the history of mathematics in Lithuania - Banionis, Juozas (Lietuvos matematikos rinkinys, 2013)
Amelija Mažylytė was the first Lithuanian diplomaed woman mathematician, the graduate of Lithuanian University, the participant of catholic women movement and also the graduate of philosophy studies. She started dissemination of the knowledge of the history of mathematics in the Lithuanian language. The article presents a complemented biography of A. Mažylytė and the works of her research interest. The special attention is given to publications about the history of calculations, the development of geometry and a universally known specialist of mathematics C.F. Gauss.